Case report: Pyrotinib and tegafur combined with radiotherapy achieved notable response in HER2-amplified rectal cancer with multiple metastases after multiline treatments - Huang, Peng; Wen, Feng; Wang, Xin (Frontiers in Pharmacology, 2024)
Metastatic colorectal cancer (mCRC) is characterized by significant phenotypic heterogeneity at the molecular level and presents a poor prognosis. Chemotherapy is commonly employed as the primary treatment option. Nevertheless, the advantages of chemotherapy are constrained, underscoring the critical necessity for novel treatment protocols aimed at enhancing patient outcomes. Human epidermal growth factor receptor 2 (HER2) has been recognized as a promising therapeutic target in mCRC. Pyrotinib, an innovative irreversible dual tyrosine kinase inhibitor targeting HER2, effectively inhibits cancer progression in various types of human cancers. Here, we present a case of a 39-year-old female with metastatic rectal cancer showing amplification of HER2. Despite resistance to multiple therapies, including trastuzumab and pertuzumab, the patient exhibited a remarkable therapeutic response to pyrotinib, tegafur combined with radiotherapy. This case provides evidence for the feasibility and potential efficacy of deploying pyrotinib in the salvage treatment of mCRC patients with HER2 amplification even though resistant to other anti-HER2 drugs.